The impact of electronic and fashion innovativeness and perceived value on online purchase intention toward the brand ‘Shein’ with trust as the moderating variable - Aspilla, Noel R. (Animo Repository, 2021)
During this era of technology, a vast number of innovations have made significant changes to the lives of many. Among the benefits of technology are the numerous online platforms that we can now access digitally, including online shopping platforms that changed the way of traditional shopping, especially now that the world is facing a global crisis due to the worldwide pandemic. As e-commerce expands, more studies continue to seek and identify the factors that motivate online shopping behavior. This research aims to study the impact of electronic innovativeness, fashion innovativeness, and perceived value on the online purchase intention of SHEIN customers while being moderated by trust. The first independent variable, electronic innovativeness, refers to the willingness of consumers to use digital technologies (Kuo & Yen, 2009), and this study will refer to it as SHEIN consumers’ perceived willingness to use digital technologies, specifically SHEIN’s website and mobile application. In addition, its antecedent will be Domain-Specific Innovativeness from the study of Citrin et al. (2000). Next, fashion innovativeness describes the willingness of a consumer to purchase the latest fashion item ahead of other consumers (Goldsmith & Flynn, 1992 and Goldsmith, 2000 as cited in Baker et al., 2019). It will refer to the extent to which the consumers, specifically first buyers, would be willing to embrace the fashionable products offered by SHEIN for this research. In addition, its antecedents are innovative personality and information-seeking behavior, from the study of Muzinich et al. (2003). The third independent variable, perceived value, was defined as the point when consumers assess whether a product or service is worth their money or not (Othman et al., 2017). Also, Escobar-Rodriguez & Bonson-Fernandez (2017) identified time-saving and cost-saving as their antecedents. In this study, perceived value will refer to the consumers’ perceived worth of purchasing fashion items online via SHEIN’s website or mobile application instead of traveling to brick-and-mortar fashion stores. For the moderating variable of this study, trust would refer to the willingness of the consumers to transact online despite the possible risks and consequences, especially using SHEIN’s website and mobile application. Its antecedents are perceived security and information quality. Lastly, the online purchase intention, which is the dependent variable of this study was defined as the intention of a consumer to purchase a good or service from his chosen brand after his evaluation (Khan et al., 2012, as cited in Putro & Haryanto, 2015). It will refer to the intention of SHEIN consumers to repurchase from the brand for this research. With a quantitative method of gathering data, using survey questionnaires from Google Forms, a total sample of 120 SHEIN consumers from Biñan City, Laguna, with ages between 16 and 60 years old, were chosen as survey respondents. Data were further analyzed by using descriptive tools such as frequency table & bar graphs and mean explanation table, and statistical tests such as Cronbach’s alpha value, Pearson’s correlation, simple linear regression, multiple linear regression, and moderated regression. In addition, a qualitative method of interviewing 10 participants was conducted to interpret, compare, and contrast with the quantitative data. Results show that electronic innovativeness, fashion innovativeness, and perceived value have a significant positive effect on online purchase intention. Furthermore, the moderating effect of trust is insignificant in the relationship between electronic innovativeness & online purchase intention and perceived value & online purchase intention. However, it has a significant moderating effect in the relationship between the independent & dependent variables and fashion innovativeness & online purchase intention.